Explaining factors contributing to alcohol consumption among elderly men: a qualitative study. - Bazrafshan, Mohammad-Rafi; Mansouri, Amir; Salmani, Abbas; Masmouei, Behnam; Kavi, Esmaeil; Elahi, Maasumeh; Barghi, Omid (Journal of Substance Use, 2025)
Background: With an increase in the elderly population, there is a greater need to pay attention to the problems of this group. This study aims to determine the influencing factors on alcohol consumption in elderly men. Methods: In this qualitative design, data were collected on 31 men older than 65 years and with at least mild dependence on alcohol using semi-structured interviews. The participants in the study were chosen using purposive and snowball sampling methods. The content analysis approach was used to analyze the data. Results: The data analysis revealed two main categories: (1) trigger events with two sub-categories of internal (beliefs about achieving goals, alcohol use experience in youth, desire to drink alcohol, low self-esteem) and external factors (peer connectedness, availability of alcohol, family member's alcohol consumption, allowed to consume at home, having a reasonable price, participating in events) and (2) reinforcing events with two sub-categories of physical (having physical pain, sleep problem, increase the effect of drugs, fatigue) and psychological factors (enhancing mood, coping with stress, feeling alone, depression, anxiety, sense of emptiness, recent bereavements). Conclusions: It is possible to prevent excessive consumption of alcoholic beverages and related complications by identifying the factors that initiate and enhance alcohol consumption in old age.